Photo Thermal Diffusion of Excited Nonlocal Semiconductor Circular Plate Medium with Variable Thermal Conductivity - Shreen El-Sapa; Khaled Lotfy; Alaa A. El-Bary; M. H. Ahmed (Advances in Condensed Matter Physics)
To examine the effects of the nonlocal thermoelastic parameters in a nanoscale semiconductor material, a novel nonlocal model with variable thermal conductivity is provided in this study. The photothermal diffusion (PTD) processes in a chemical action are utilized in the framework of the governing equations. When elastic, thermal, and plasma waves interact, the nonlocal continuum theory is used to create this model. For the main formulations to get the analytical solutions of the thermal stress, displacement, carrier density, and temperature during the nanoscale thermo-photo-electric medium, the Laplace transformation approach in one dimension (1D) of a thin circular plate is utilized. To create the physical fields, mechanical forces and thermal loads are applied to the semiconductor’s free surface. To acquire the full solutions of the research areas in the time-space domains, the inverse of the Laplace transform is applied with several numerical approximation techniques. Under the impact of nonlocal factors, the principal physical fields are visually depicted and theoretically explained.